(untitled) (Journal of Global Arts Studies, 2024)
Background: Artificial Intelligence (AI) is triggering a revolution in knowledge and technology, profoundly influencing various industries, including education. Countries around the world are actively exploring the application of AI in education; however, this process is also accompanied by numerous challenges. Objective: This study aims to conduct a comprehensive analysis of the current status, opportunities, and challenges of AI applications in education in order to provide both theoretical and practical guidance for promoting the sustainable development of education in the AI era. Methods: Using the method of literature review, this study collects and analyzes a wide range of relevant academic literature, supplemented by case analysis through in-depth examination of several representative educational practices involving AI technologies. Results: The findings indicate that the application of artificial intelligence in education has already achieved significant results. Nevertheless, major challenges remain, including outdated policies and regulations, unequal educational opportunities, ethical concerns related to technology, the need for teacher professional development, and the necessity of reforming educational content and teaching methods. Conclusion: In the era of artificial intelligence, the sustainable development of education requires collaborative efforts from governments, educational institutions, teachers, and society as a whole. Governments should accelerate the improvement of policies and regulations, prioritize educational equity, and establish unified technical standards and ethical norms. Teachers need to strengthen their professional competence and innovate in teaching practices. Only through coordinated cooperation can all stakeholders fully utilize the advantages of AI, overcome existing challenges, and achieve intelligent, equitable, and sustainable educational development.